Greater consumption of protein‐poor anthropogenic food by urban relative to rural coyotes increases diet breadth and potential for human–wildlife conflict. Issue 12 (26th March 2015) - Murray, M.; Cembrowski, A.; Latham, A. D. M.; Lukasik, V. M.; Pruss, S.; St Clair, C. C.
Abstract : Reports of encounters between people and generalist urban‐adapted carnivores are increasing around the world. In North America, coyotes Canis latrans are among the carnivores that appear to be especially capable of incorporating novel anthropogenic food types, including those found in cities. Consuming anthropogenic food may benefit coyotes by increasing their dietary diversity, but it may also lead to increased interactions and conflicts with humans. To test these hypotheses, we compared the diets of urban and rural coyotes from two urban and three rural sites spanning 32 200 km 2 in Alberta, Canada. We analyzed scat samples to calculate diet diversity at the level of both individuals (species per scat) and populations (Shannon index) and to determine the frequency of anthropogenic food consumption. We complemented this comparison with stable isotope analyses of hair samples taken from individual urban and rural coyotes that were or were not reported by the public for repeatedly visiting backyards and schoolyards during the day. Relative to rural coyotes, urban coyotes had more diverse diets at the level of both individuals and populations, consumed anthropogenic food more often, and animals less often, than rural coyotes. Although urban coyotes assimilated more anthropogenic food than the rural coyotes overall, the urban coyotes reported for conflict assimilated less protein and were more likely to be diseased. Our results suggest that processed anthropogenic food may contribute to the success of urban coyotes, but does not entirely correlate with conflict. Instead, some seemingly innocuous, but low‐protein food sources such as bird feeders, compost, and cultivated fruit trees may contribute disproportionately to encounters with people for coyotes and other urban‐adapted opportunistic carnivores.